Large indoor cage study of the suppression of stable Aedes aegypti populations by the release of thiotepa-sterilised males - Gato, René (Instituto Oswaldo Cruz, Ministério da Saúde, 2014)
The sterile insect technique (SIT) is a promising pest control method in terms of efficacy and environmental compatibility. In this study, we determined the efficacy of thiotepa-sterilised males in reducing the target Aedes aegypti populations. Treated male pupae were released weekly into large laboratory cages at a constant ratio of either 5:1 or 2:1 sterile-to-fertile males. A two-to-one release ratio reduced the hatch rate of eggs laid in the cage by approximately a third and reduced the adult catch rate by approximately a quarter, but a 5:1 release drove the population to elimination after 15 weeks of release. These results indicate that thiotepa exposure is an effective means of sterilising Ae. aegypti and males thus treated are able to reduce the reproductive capacity of a stable population under laboratory conditions. Further testing of the method in semi-field enclosures is required to evaluate the mating competitiveness of sterile males when exposed to natural environmental conditions. If proven effective, SIT using thiotepa-sterilised males may be incorporated into an integrated programme of vector control to combat dengue in Cuba.